Creatine use and exercise heat tolerance in dehydrated men - Watson, G.; Casa, D. J.; Fiala, K. A.; Hile, A.; Roti, M. W.; Healey, J. C.; Armstrong, L. E.; Maresh, C. M. (Journal of Athletic Training, 2006)
Context: Creatine monohydrate (CrM) use is highly prevalent in team sports (eg, football, lacrosse, ice hockey) and by athletes at the high school, college, professional, and recreational levels. Concerns have been raised about whether creatine use is associated with increased cramping, muscle injury, heat intolerance, and risk of dehydration.